Kloning Gen Transcriptional Activator Protein dan Replication-Associated Protein dari Squash leaf curl China virus Penyebab Penyakit Daun Kuning pada Tanaman Mentimun - Ni Nengah Putri Adnyani; I Dewa Made Putra Wiratama; I Gede Rai Maya Temaja; Sari Nurulita; Gede Suastika (Jurnal Fitopatologi Indonesia, 2018)
Yellow disease on Cucurbitaceae caused by Squash leaf curl China virus (SLCCNV; Begomovirus) is an important disease in many countries. Typical yellow leaf curl symptoms was found on cucumber in Tabanan, Bali. The objective of this research is to clone Transcriptional Activator Protein (TrAp) and Replication-Associated Protein (Rep) of SLCCNV Indonesian isolate. Universal primer for Begomovirus, i.e. SPG1/SPG2 was used to amplify DNA fragment of Begomovirus which cover the TrAp and Rep gene. The amplicon of ± 912 bp in size was then cloned into pTZ57R/T plasmid vector by TA-cloning method to obtain plasmid recombinant pTZ-SLCCNV. The plasmid recombinant was successfully confirmed by PCR colony and DNA sequencing. The nucleotide sequences analysis of plasmid recombinant showed highest homology (98%) of the corresponding gene to pumpkin isolate of SLCCNV from Malaysia.